Subjective Well-Being across the Lifespan in Europe and Central Asia - Bauer, Jan Michael; Levin, Victoria; Munoz Boudet, Ana Maria; Nie, Peng; Sousa-Poza, Alfonso (World Bank, Washington, DC, 2015)
This paper uses data from the Integrated Values Survey, the Life in Transition Survey, and the Russia Longitudinal Monitoring Survey to analyze the relation between age and subjective well-being in the Europe and Central Asia region. Although the results generally confirm the findings of previous studies of a U-shaped relation between subjective well-being and age for most of the lifecycle, the paper also finds that well-being declines again after people reach their 60s and 70s, giving rise to an S-shaped relation across the entire lifespan. This pattern generally remains robust for most of the cross-sectional and panel analyses. Hence, despite significant heterogeneity in the pattern of well-being across the lifespan in the Europe and Central Asia region, the paper does not observe high levels of cross-country or cross-cohort variation.